Tanshinone IIA inhibits HIF-1α and VEGF expression in breast cancer cells via mTOR/p70S6K/RPS6/4E-BP1 signaling pathway. - Guobing Li; Changyu Shan; Lei Liu; Ting Zhou; Jing Zhou; Xiaoye Hu; Yibiao Chen; Hongjuan Cui; Ning Gao (PLoS ONE)
Hypoxia-inducible factor 1α (HIF-1α) and vascular endothelial growth factor (VEGF) play important roles in angiogenesis and tumor growth. Tanshinone IIA (T2A) is a novel antiangiogenic agent with promising antitumor effects; however, the molecular mechanism underlying the antiangiogenic effects of T2A remains unclear. In the present study, we provided evidence showing that T2A inhibited angiogenesis and breast cancer growth by down-regulating VEGF expression. Specifically, T2A repressed HIF-1α expression at the translational level and inhibited the transcriptional activity of HIF-1α, which led to the down-regulation of VEGF expression. Suppression of HIF-1α synthesis by T2A correlated with strong dephosphorylation of mammalian target of rapamycin (mTOR) and its effectors ribosomal protein S6 kinase (p70S6K) and eukaryotic initiation factor 4E-binding protein-1 (4E-BP1), a pathway regulating HIF-1α expression at the translational level. In addition, we also found that T2A inhibited the angiogenesis and growth of human breast cancer xenografts in nude mice through suppression of HIF-1α and VEGF. Our study provides novel perspectives and potential targets for the treatment of human breast cancer.